Comparative analysis of Oil obtained from Moringa and Neem Seeds - Garba, L; Mahmoud, A.A; Boryo, D. E. A; Abubakar, A; Abdullahi Z. A (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2024)
This study reports the extraction of oil from moringa and neem seeds using soxhlet extractor and the production of biodiesel from the two oils extracted and compared with fossil diesel in terms of physico-chemical properties and cost of production. The biodiesels were produced by transesterification reaction with alcoholic KOH at 900C temperature. From the results obtained it was found that the yield of biodiesel from moringa seed oil (48%) is less when compared with that neem seed oil (52%). It was found that the chemical properties of moringa and neem oils were, such as saponification, (196, 182) iodine value, (62.51, 83.4) specific gravity (0.71, 0.94) peroxide value, (1.22, 1.07) acid value, (0.62,0.47) density, (0.72, 0.81) viscosity, (2.3, 4.2) when compared with the ASTM D 445 standard limit. The physical properties of the raw extracted oil and the biodiesel produced for moringa, neem and fossil diesel for flash point (149°C, 111°C, and 97°C), pour point (8°C, 5°C and 7°C) and cloud point (16°C, 9°C and 7°C) comparatively with the standard fossil fuel. The FT-IR result revealed the presence of SP3 C-H (stretch) at 2923.81 cm-1, C=O stretching vibration at 1746.67 cm-1 indicating the presence of carbonyl group, stretch vibrations at 3007.32 cm-1 showing the presence of aromatic SP2 C-H. Also HC=O stretching at 2853.67 cm-1 was observed indicating the presence of aldehyde, the presence of HC =CH bend at 667.24 cm-1 indicates the presence of alkenes. The peak observed at 3564.19 cm-1 indicates the presence of O-H, the peak observed at 1195.50 cm-1 was assigned to C-O bend indicating the presence of carboxylic acid/esters. The moringa biodiesel contain more of fatty acids and the neem biodiesel contain more of esters due to esterification of the neem oil as revealed by through GC-MS spectrum of the neem oil. The neem oil cannot contain fatty acid due to the absent of the O-H (stretch) band on its FT-IR spectrum. The relative quantification is obtained from the chromatogram of both oil in GC-MS spectrum. The result showed that neem oil could be uses as an alternative to fossil diesel if large scale of production is employ.